The alterations of leg joint angular displacements and muscle co-contraction at landing following various aerial catching movements - Ting Wang; Penglei Fan; Shuai Wang; Youngsuk Kim; Sukwon Kim (Journal of Men's Health, 2025)
Background: Jump-landing is a major cause of lower limb injuries. This study investigated the effect of various aerial catching movements on the co-contraction index (CCI) of the knee and ankle muscles, as well as on joint angular displacements and joint moments during landing. Methods: Fifteen right-hand dominant collegiate basketball players (age: 21.0 ± 1.2 years; weight: 79.9 ± 7.9 kg; height: 180.9 ± 5.5 cm; training experience, 5.6 ± 3.5 years) performed maximal countermovement jumps under four conditions: no catching (NC), right (RULC), left (LULC) and bilateral (BULC) upper-limb catching. Electromyography of the rectus femoris (RF), biceps femoris (BF), lateral gastrocnemius (LG) and tibialis anterior (TA), along with kinematic and kinetic data, were recorded during landing. The co-contraction index (CCI) of knee and ankle muscles before and after landing, as well as angular displacements and peak joint moments were calculated. Results: When compared to the NC condition, all aerial catching movements resulted in reduced knee flexion (RULC, p = 0.004, d = −1.11; LULC, p < 0.001, d = −1.52; BULC, p = 0.013, d = −0.97) and increased ankle dorsiflexion (RULC, p = 0.002, d = −1.21; LULC, p = 0.004, d = −1.13; BULC, p < 0.001, d = −1.50) angular displacement after landing, along with significantly higher CCI of RF-BF (RULC, p = 0.018, d = 0.93; LULC, p = 0.033, d = 0.85; BULC, p = 0.042, d = 0.81) and LG-TA (RULC, p = 0.025, d = 0.88; LULC, p = 0.004, d = 1.12; BULC, p = 0.015, d = 0.95) before landing, the LULC condition led to greater knee abduction angular displacement (p = 0.002, d = 1.19) and moment (p = 0.001, d = 1.26), and lower RF-BF CCI after landing (p = 0.037, d = 0.83). Aerial catching movements increased lower limb muscle co-contraction before landing and led to greater knee stiffness after landing. However, LULC reduced knee co-contraction and increased frontal plane knee motion after landing, indicating decreased joint stability and higher injury risk. Conclusions: Injury prevention programs should incorporate upper limb coordination and perturbation training—especially for the left arm—to enhance motor control and joint stability during sport-specific tasks.